2016
DOI: 10.5935/abc.20160089
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon Treatment of Very Late Stent Thrombosis Due to Complicated Neoatherosclerosis

Abstract: We describe the treatment of a patient presenting with very-late stent thrombosis with the use of a drug-coated balloon. In this patient, optical coherence tomography disclosed that ruptured and complicated neoatherosclerosis was the underlying substrate responsible for the episode of very-late stent thrombosis. The potential use of drug-coated balloons in this unique scenario is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This indicates that DCB may not be fully effective in STEMI with high thrombus burden and that DCB may be useful for treating ISR with thrombosis. In a previous case report about the treatment of a patient presenting with very late ST with the use of a DCB, DCB angioplasty might be effective and considered in treatment for very late ST as a result of neoatherosclerosis [10]. In our case, both excessive neointimal proliferation in the distal stent and incomplete neointimal healing with a massive thrombus in the proximal stent were observed when LST occurred.…”
Section: Discussionmentioning
confidence: 57%
“…This indicates that DCB may not be fully effective in STEMI with high thrombus burden and that DCB may be useful for treating ISR with thrombosis. In a previous case report about the treatment of a patient presenting with very late ST with the use of a DCB, DCB angioplasty might be effective and considered in treatment for very late ST as a result of neoatherosclerosis [10]. In our case, both excessive neointimal proliferation in the distal stent and incomplete neointimal healing with a massive thrombus in the proximal stent were observed when LST occurred.…”
Section: Discussionmentioning
confidence: 57%
“…DCB use markedly inhibits late neointimal formation. A previous study demonstrated how DCB potentially provides an attractive therapeutic strategy for neoatherosclerosis . However, another study reported that neoatherosclerosis can develop after DCB treatment for ISR …”
Section: Discussionmentioning
confidence: 99%